A comparative outline for quantifying risk ratings in occupational health and safety risk assessment. (20th September 2018) - Gul, Muhammet; Ak, M. Fatih
Abstract: The concept of risk assessment has been introduced as an examination of safety in the workplace to enable assessments as to whether sufficient precautions have been taken or if more should be done to prevent potential harm. Hazardous industries have faced serious fatalities related to work, workplaces, and workers as a consequence of their high-risk processes. Therefore, in this work, a novel and comparative methodology for quantifying risk ratings in occupational health and safety risk assessment is proposed. A 5 × 5 risk matrix is initially determined, and the fuzzy technique for order preference by similarity to ideal solution (FTOPSIS) method is then applied to rank identified hazards. As a novelty to the knowledge, two parameters of the 5 × 5 matrix method, likelihood and severity, are subjectively assessed by occupational health and safety experts, and then importance levels for these parameters are determined using the Pythagorean fuzzy analytic hierarchy process (PFAHP). In the proposed approach, analysts use linguistic terms and Pythagorean fuzzy sets, which provide greater independence in their evaluations. An outline that enables comparison of the results of this study with the circumcenter of centroids method and the fuzzy AHP-fuzzy VIKOR integrated method in quantifying risk ratings is also provided. In order to present the practicality of this work, a case study in an underground copper and zinc mine is carried out. Highlights: A comparative outline in occupational health & safety risk assessment is proposed. A case study is carried out for an underground copper and zinc mine. PFAHP is used in weighting risk parameters of 5 × 5 matrix method. The prioritization of hazards is determined by FTOPSIS method. A comparison with Circumcenter of Centroids and integrated FAHP-FVIKOR is provided.